Production Elasticity of Layer Farming During the COVID-19 Pandemic in Blitar District - Santoso, Gunawan Adi; Hartono, Budi; Suwandi, Umi Wisaptiningsih (Faculty of Animal Science, Universitas Brawijaya, 2024)
The livestock sub-sector, an integral part of the agricultural sector, is the animal protein producing sub-sector which plays an important role in meeting people's nutritional needs. The development of the laying hen farming business has enormous potential, this is because purebred chicken eggs contribute quite a lot to animal protein self-sufficiency. The research aims to analyze the input factors of the production that affect the production of layer farming businesses and to assess the production elasticity of these businesses during the COVID-19 pandemic in Blitar District. Data collection took place between July and August 2020 in the Blitar Distrcit. Utilizing a sample random sampling method. The study involved 64 farmers as representative. The research variables used in this study were the population of laying hens, the price of chicken eggs, feed costs, vaccines and medicines expenses, seed prices, mortality, electricity costs, the price of culled chickens, Hen Day Production (HDP) and the number of workers. Quantitative analysis was employed to analyze production costs, revenues, and income, while qualitative analysis was used to analyze production elasticity through Cobb-Douglas regression analysis. The research data were processed using SPSS version 24. The results of the study indicate that 1) the population of laying hens and HDP significantly affected the production of layer farming businesses, along with the cost of vaccines and medications in the Blitar District. 2) The population of layers, mortality rates, electricity costs, HDP, and total labor demonstrated elasticity with respect to the production of layer farms. Conversely, egg prices, feed costs, vaccination and medication expenses, day-old chick (DOC) costs, and final chicken prices exhibited inelasticity concerning the production of layer farms in Blitar district.